Relative Risk Assessment of Intrauterine Infection of the Fetus During Cytomegalovirus Infection in Early Pregnancy - K. K. Petrova (Acta Biomedica Scientifica)
Background. Intrauterine fetal infection (IUI), the common cause of which is the cytomegalovirus (CMV), occupies one of the first places in the structure of perinatal morbidity and mortality. There are no data on the relative risk assessment of IUI at the exacerbation of CMV infection and its delitescent course in first trimester of pregnancy in the literature.Aim: to calculate the relative risks of fetal IUI in pregnant women with exacerbation of CMV infection in the first trimester of pregnancy.Methods. A retrospective review of the labor and delivery medical records and prenatal records of 104 CMV-seropositive women was carried out. Fifty of these women had an exacerbation of CMV infection in the first trimester of pregnancy – main group and 54 of them were with delitescent course of the disease (comparison group).Results. A comparative analysis of ultrasound and morphological markers of IUI with risk assessment depending on the course of CMV infection in the first trimester of pregnancy has been carried out. A high risk of placental structure abnormalities, as well as amniotic fluid and fetal membranes, fetal and placental blood flow pathology, onset of  choroid plexus cyst and fetal growth restriction was found, with a statistically significant difference in the group of pregnant women with exacerbation of CMV infection in the first trimester of pregnancy.Conclusion. The findings suggest that the exacerbation of CMV infection in early pregnancy is a risk factor for IUI.